2013
DOI: 10.1016/j.jmbbm.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Insight into differences in nanoindentation properties of bone

Abstract: Nanoindentation provides the ideal framework to determine mechanical properties of bone at the tissue scale without being affected by the size, shape, and porosity of the bone. However, the values of tissue level mechanical properties vary significantly between studies. Since the differences in the bone sample, hydration state, and test parameters complicate direct comparisons across the various studies, these discrepancies in values cannot be compared directly. The objective of the current study is to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
70
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 36 publications
6
70
2
2
Order By: Relevance
“…Young's modulus, as measured by NI test in this study, was in the range of 13.32 GPa to 38.15 GPa, which was similar to or slightly higher than the moduli determined in previous NI studies that measured the tibia and femurs of mice [33][34][35][36][37] (Table 2). It has been indicated that the bone elastic modulus obtained from NI was generally lower under wet conditions than in the dry state [36,[38][39][40].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Young's modulus, as measured by NI test in this study, was in the range of 13.32 GPa to 38.15 GPa, which was similar to or slightly higher than the moduli determined in previous NI studies that measured the tibia and femurs of mice [33][34][35][36][37] (Table 2). It has been indicated that the bone elastic modulus obtained from NI was generally lower under wet conditions than in the dry state [36,[38][39][40].…”
Section: Discussionsupporting
confidence: 86%
“…It has been indicated that the bone elastic modulus obtained from NI was generally lower under wet conditions than in the dry state [36,[38][39][40]. However, in the previous studies, the samples were first dried, followed by rehydration, after at least 24 hours of immersion in various solutions, such as 3.7% formaldehyde, 4% paraformaldehyde, Ringer's solution, and ethanol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…h f can be represented as the plastic deformation (he) (Bhushan & Li, 2003;Ferguson, 2009). The elastic deformation (he) can be defined as the difference between the maximum displacement and the final displacement -Floreza et al, 2013).…”
mentioning
confidence: 99%